Administration of the early childhood care and development (ECCD) checklist by child development workers (CDWs) in the province of Bataan - Domingo, Joan Therese R. (College of Home Economics, University of the Philippines Diliman, 2019)
This descriptive-exploratory research aimed to describe the practices in administering the ECCD checklist of Child Development Workers in the Province of Bataan. A qualitative approach was employed with interview as the data collection method. Thirty (30) Child Development Workers were randomly selected for the interview. Interview results showed that majority of the CDWs are knowledgeable of the nature and purpose of the checklist. They use the tool for assessing and monitoring the child's development over a period of time. With regards to the administration of the checklist, majority of the CDWs administer the checklist according to standard procedure. The CDWs use various methods and strategies as they go through the process of introducing the checklist to the parents, preparing the children for assessment and administering each assessment item the way it is sequenced in the checklist. For the scoring and interpretation of the results, results revealed that majority of the CDWs uses standard markings to score assessment items and uses the interepretation table provided in the ECCD checklist to get the narrative interpretation of the numerical results. For the uses of the checklist, results are used for three things: for teaching, for monitoring and for the child's portfolio. These uses aims to assist the child develop his/her capabilities. Results also showed that CDWs recognize the need for collaboration between parents and CDW to help the child in his/her development. With regards to interventions, CDW uses tried and tested interventions. Majority of the CDWs did not experience or were able to overcome challenges in using the checklist because of availability of manual, continuous capability building activities and Tagalog-translated checklist.